2004
DOI: 10.1128/iai.72.5.2556-2563.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exacerbates Murine Pulmonary Tuberculosis

Abstract: Alcohol consumption has been described as a risk factor for infection with Mycobacterium tuberculosis, but its contribution to tuberculosis has been difficult to isolate from other adverse socioeconomic factors. Our objective was to evaluate the impact of alcohol consumption on pulmonary infection with M. tuberculosis in a murine model. BALB/c mice were maintained on the Lieber-DeCarli liquid ethanol diet or a liquid control diet and infected intratracheally with low-dose M. tuberculosis H37Rv. Lung organism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 44 publications
3
49
0
3
Order By: Relevance
“…These observations have since then been confirmed by epidemiological and laboratory studies (MacGregor et al, 1978;Mason et al, 2004;Saitz et al, 1997;Schmidt and De Lint, 1972;Zaridze et al, 2009). More recently, alcohol abuse has also been associated with increased incidence and severity of acute respiratory distress syndrome (ARDS) (Esper et al, 2006;Moss et al, 1996), increased risk for viral and fungal infections and, subsequent susceptibility to secondary bacterial infections (Fong et al, 1994;Jerrells et al, 2007).…”
Section: Alcohol Modulates Immune Response During Bacterial and Viralsupporting
confidence: 59%
See 1 more Smart Citation
“…These observations have since then been confirmed by epidemiological and laboratory studies (MacGregor et al, 1978;Mason et al, 2004;Saitz et al, 1997;Schmidt and De Lint, 1972;Zaridze et al, 2009). More recently, alcohol abuse has also been associated with increased incidence and severity of acute respiratory distress syndrome (ARDS) (Esper et al, 2006;Moss et al, 1996), increased risk for viral and fungal infections and, subsequent susceptibility to secondary bacterial infections (Fong et al, 1994;Jerrells et al, 2007).…”
Section: Alcohol Modulates Immune Response During Bacterial and Viralsupporting
confidence: 59%
“…In this same model of infection, the expression of IL-17, a cytokine which serves as a link between innate and adaptive immunity, is shown to be inhibited by chronic alcohol intake . In mouse models of tuberculosis, excessive alcohol feeding impaired pathogen clearance, blunted CD4+ and CD+ T lymphocyte responses, decreased lymphocyte proliferation, and IFN-c levels in CD4+ T (Mason et al, 2004). Similarly, decreased ability to clear respiratory syncytial virus (RSV) infection despite increased IFN-a and IFN-b induction, progressive loss of CD+ T cells, increased injury and lethality along with increased inflammation reported in animal models of chronic alcohol feeding (Jerrells et al, 2007).…”
Section: Alcohol Modulates Immune Response During Bacterial and Viralmentioning
confidence: 99%
“…Moreover, mice fed up to 20% ethanol for 5 weeks were still considered healthy enough to tolerate experiments (40,41) prior to infection with S. pneumoniae (41) or Mycobacterium tuberculosis (40). Therefore, this ethanol feeding procedure is suitable for experiments evaluating the effects of alcohol.…”
Section: Figmentioning
confidence: 99%
“…Animal studies of pulmonary TB have shown decreased lung CD4 and CD8 T cells and diminished proliferation in ethanol-fed mice compared with a control group. [12] In another study, ethanol also significantly decreased the granulomatous response. This was possibly caused by impaired interferongamma (IFN-γ) secretion of T cells that were isolated from the lungs and the mediastinal lymph nodes of the alcohol-consuming mice.…”
Section: Discussionmentioning
confidence: 99%